METAPHOR AS OBJECT OF LINGUOCULTURAL STUDY IN UZBEK LANGUAGE - Karjawbaev Orazali Esbosinuli; Toleubayeva A.O. (Journal of new century innovations, 2024)
Abstract: The varieties of metaphors seen in literature and their linguocultural characteristics are explained in the article. The metaphor's linguistic quality is contrasted with alternative methods of movement, specifically the similarity. Examples from Togay Murad's "Oydinda yurgan odamlar" clarify this idea in relation to the ethnocultural components of migrating units.